LITERATUR REVIEW: INTERVENSI TERAPI UNTUK ANAK SEBAGAI TRAUMA HEALING - Cindya, Nada; Anita, Ayu (Coping: Community of Publishing in Nursing; Vol 11 No 1 (2023): Februari 2023DO - 10.24843/coping.2023.v11.i01.p01, 2023)
Disasters have the greatest impact on the most vulnerable groups, especially the age group of children, where in this situation both in the community and in the scope of the children's clinic, there is worrying anxiety pressure. So that appropriate therapeutic interventions are needed in dealing with these problems through play therapy strategies that can help reduce children's anxiety. This study aims to examine the literature related to play therapy that health workers can do in dealing with anxiety in children. The process of searching for articles for the preparation of this literature review used the PICO search strategy regarding the types of play therapy that can be used to address children's anxiety in clinical settings where the search was carried out using four databases including Ebsco, Sage, Sciencedirect, and ProQuest. From 541 articles from four search databases, two articles were finally selected to be used in this literature study. Where therapy is involved in the form of puzzle games and therapy presents pets. Through play therapy strategies using various media such as puzzles and presenting pet visits to be a solution for children to help reduce their anxiety.